High-frequency low-loss manganese zinc ferrite material and preparation method thereof

By adjusting the composition and preparation process of manganese-zeb ferrite materials, especially introducing thermal aging treatment steps, the internal stress of the material is reduced, and the problems of high power loss and insufficient durability of manganese-zeb ferrite under high-frequency conditions are solved, and the improvement of low loss and high-frequency performance is achieved.

CN119638397AInactive Publication Date: 2025-03-18ZHEJIANG UNIV OF TECH

Patent Information

Application Number
CN202411890296.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing manganese-zeb ferrite materials have high power loss under high frequency conditions and are insufficient durability, making it difficult to meet the needs of low loss and high frequency performance in electronic information industries such as 5G communications, computers and networks.

Method used

A high-frequency, low-loss manganese ferrite material is prepared by adopting a method of preparation, including ingredients, wet ball milling, pre-firing, secondary ball milling, granulation, molding, sintering and thermal aging treatment. By adjusting the components and process parameters, the internal stress of the material is reduced and the magnetic properties are improved.

Benefits of technology

Under 1MHz and 50mT conditions, the power loss of the material is not higher than 40kW·m-3 and 50kW·m-3, and at 3MHz and 30mT losses are not higher than 260kW·m-3 and 340kW·m-3, which significantly reduces the power loss at high frequencies and improves the durability of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119638397A_ABST
    Figure CN119638397A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of soft magnetic ferrite, and discloses a high-frequency low-loss manganese zinc ferrite material and a preparation method thereof, and the manganese zinc ferrite material comprises main components and auxiliary components. The main components comprise ferric oxide, zinc oxide, manganese oxide and cobaltosic oxide. The auxiliary components comprise calcium carbonate, silicon dioxide and tantalum pentoxide. The preparation method of the manganese zinc ferrite material comprises the following steps: proportioning, drying and ball-milling; pre-sintering is performed; performing secondary ball milling; performing granulation; forming is conducted; sintering is performed; and performing thermal aging. The manganese-zinc ferrite prepared by the invention has relatively low power loss under a high-frequency condition, and can be applied to the field of electronic materials related to power conversion, such as transformers and inductors.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of soft magnetic power ferrite, and relates to a high-frequency low-loss manganese-zinc ferrite material and a preparation method thereof. Background Art

[0002] Manganese-zinc ferrite is a common soft magnetic material, which generally has the characteristics of high saturation magnetization, high magnetic permeability, and low loss. Therefore, it is widely used in the electronics industry, such as the development of transformer cores, high-frequency inductors, and microwave components. In recent years, with the rapid development of electronic information industries such as 5G communications, computers and networks, and new energy vehicles, the demand for power electronic devices has increased day by day, and higher requirements have been placed on the performance of devices. Its usage scenarios have been upgraded from the original kHz level to the MHz level. Therefore, the power loss (P) of manganese-zinc ferrite at high frequencies has been reduced. cv ) has become an urgent need. At the same time, the Curie temperature of manganese-zinc ferrite is relatively low. This characteristic leads to a narrow applicable temperature range of manganese-zinc ferrite. Under long-term and high-intensity use, the magnetic properties will decrease due to heat. Therefore, improving the durability of manganese-zinc ferrite is also an urgent problem to be solved.

[0003] In order to obtain lower power loss, the method of changing the composition of manganese-zinc ferrite is usually adopted. The composition of manganese-zinc ferrite includes two parts: main component and auxiliary component. The main component is usually composed of elements such as iron, manganese, zinc, and cobalt, and the auxiliary component is usually a small amount of non-metallic elements and rare earth elements. Manganese-zinc ferrite has a spinel structure. The iron and zinc ions in the main formula occupy tetrahedral sites, and the manganese ions occupy octahedral sites. The ions introduced by the auxiliary components can enter the spinel lattice by replacing iron ions, thereby improving the magnetic properties of ferrite.

[0004] Patent CN118299136A proposes a formula and preparation method for high-frequency low-loss manganese-zinc ferrite. The power loss of the product at 1MHz, 50mT, 25℃ and 100℃ is not more than 50kW·m -3 and 70kW·m -3 , there is still room for further reduction. At the same time, the patent mentioned that the magnetic field heat treatment method has high requirements for equipment.

[0005] Patents CN118184328A and CN118184329A all propose high-frequency, low-loss manganese-zinc ferrite and its preparation method. The former product has a minimum power loss of 200.1kW·m at 1MHz, 50mT and 25℃. -3 The latter has a power loss of 50kW·m at 1MHz, 50mT, and 25℃. -3 There is also room for further reduction.

[0006] In summary, the development of a high-frequency, low-loss manganese-zinc ferrite material and its preparation method has important application value. Summary of the invention

[0007] The purpose of the present invention is to provide a high-frequency low-loss manganese-zinc ferrite material and a preparation method thereof in view of the deficiencies in the prior art.

[0008] The technical solution adopted by the present invention is:

[0009] A method for preparing high-frequency low-loss manganese-zinc ferrite comprises the following steps:

[0010] 1) Batching and mixing. The main components are accurately weighed according to the proportion and mixed with deionized water, and wet ball milled to obtain a uniformly distributed slurry. The mass ratio of deionized water used is 1.5:1 to 2.5:1 to the mass of powder, and the ball milling time is 16h to 24h. After the slurry is dried, a powder with uniform particle distribution is obtained; wherein the main components, in molar percentage, include Fe2O3: 54.75~56.95mol%, ZnO: 0.26~0.32mol%, Co3O4: 0.30~0.40mol%, and the remainder is MnO;

[0011] 2) Pre-sintering. The powder obtained in step 1) is placed in a muffle furnace for pre-sintering; the pre-sintering temperature is 800°C to 900°C, the heating rate is 2°C / min, and the holding time is 3h.

[0012] 3) Secondary ball milling. Accurately weigh the auxiliary components according to the proportion, mix with the pre-burned powder obtained in step 2) and deionized water, the mass ratio of deionized water used to the powder mass is 1.5:1 to 2.5:1, the ball milling time is 16h to 24h, and wet ball milling is used to obtain a uniformly distributed slurry. After the slurry is dried, a powder with uniform particle distribution is obtained; wherein, the auxiliary components, measured by mass percentage of the main components, include CaCO3: 1400ppm to 1800ppm, SiO2: 50ppm to 100ppm, Ta2O5: 1000ppm to 1400ppm;

[0013] 4) Granulation: Add polyvinyl alcohol aqueous solution to the powder obtained in step 3), mix evenly and granulate to obtain granules, the mass concentration of the polyvinyl alcohol aqueous solution used is 6%wt-12wt%, and the mass ratio of the polyvinyl alcohol aqueous solution to the powder is 8:1-15:1.

[0014] 5) Molding. The granular material obtained in step 4) is pressed into a mold to obtain a ferrite magnetic ring green body;

[0015] 6) Sintering. The magnetic ring green body in step 5) is placed in a tube furnace for high-temperature sintering at a sintering temperature of 1160°C-1180°C for 3h-8h, and then cooled naturally. A balanced oxygen partial pressure is used during the cooling process to obtain manganese-zinc ferrite;

[0016] 7) Heat aging treatment: The ferrite magnetic ring obtained in step 6) is placed in a tube furnace for long-term heat aging treatment, the heat aging temperature is 180°C to 220°C, the heating rate is 2°C / min, and the heat aging time is 180h to 250h.

[0017] The present invention finds that the reduction of internal stress caused by the thermal aging process can further improve the magnetic properties of manganese-zinc ferrite. The preparation process of manganese-zinc ferrite includes steps such as sintering and mechanical processing, which are prone to internal stress. The existence of internal stress will cause the distortion of the internal lattice of the material, and the atoms in the lattice will deviate from the equilibrium position. Soft magnetic ferrite will produce hysteresis under the action of an alternating magnetic field, and the hysteresis loss is related to the movement of the magnetic domain wall. The lattice distortion caused by internal stress will hinder the movement of the magnetic domain wall and increase the energy barrier, so high internal stress will lead to high hysteresis loss. Thermal aging treatment provides enough energy for atoms, and the atoms that originally deviated from the equilibrium area move to the equilibrium position, reducing distortion and thus reducing hysteresis loss.

[0018] The thermal aging process will also bring about adjustments to the grain boundary structure. Grain boundaries are an important part that affects eddy current losses. For example, auxiliary components such as calcium and silicon will gather at the grain boundaries to form high-resistance grain boundaries, which significantly suppress eddy current losses. However, since the grain boundaries are transition areas between adjacent grains, internal stresses are often concentrated at the grain boundaries, which makes it easy for dislocations, vacancies and other defects to occur at the grain boundaries, affecting the grain boundary structure and changing the path of electron migration. During the thermal aging process, the atoms at the grain boundaries gain energy and rearrange themselves. After releasing the internal stress, the resistivity can be increased and the eddy current loss can be reduced.

[0019] As a further configuration of the present invention, in step 1) and step 3), the wet ball milling time is 18 hours, and the mass ratio of deionized water to powder is 2:1.

[0020] As a further configuration of the present invention, the pre-firing temperature in step 2) is 850°C.

[0021] As a further configuration of the present invention, step 4): the concentration of the polyvinyl alcohol aqueous solution is 10 wt %, and the mass ratio of the polyvinyl alcohol aqueous solution to the granular material is 10:1.

[0022] As a further configuration of the present invention, step 6) the sintering temperature is 1170° C. and the holding time is 6 hours.

[0023] As a further configuration of the present invention, in step 7), the heat aging treatment temperature is 200° C. and the heat aging time is 200 h.

[0024] As a further configuration of the present invention, the auxiliary components, calculated by weight of the main components, include CaCO3: 1400ppm-1800ppm, SiO2: 50ppm-100ppm, Ta2O5: 1000ppm-1400ppm. Preferably, CaCO3: 1600ppm, SiO2: 80ppm, Ta2O5: 1200ppm.

[0025] Compared with the existing technology, the manganese-zinc ferrite preparation technology and thermal aging process proposed in the present invention have the following beneficial effects:

[0026] 1. Through multiple systematic experiments to control the main components and auxiliary components, and continuously improve the preparation method and thermal aging process, high-frequency and low-loss manganese-zinc ferrite was prepared. Its power loss at 1MHz, 50mT at 25℃ and 100℃ is not more than 40kW·m -3 and 50kW·m -3 ; At 3MHz, 30mT, the loss at 25℃ is not higher than 260kW·m -3 , the loss at 100℃ is not higher than 340kW·m -3 . It meets the current industrial demand for low-loss manganese-zinc ferrite materials under high-frequency conditions.

[0027] 2. The thermal aging process is simple and requires low equipment. Compared with the traditional magnetic field heat treatment process, it has the advantages of low energy consumption, energy saving and environmental protection, which improves economic benefits. At the same time, thermal aging treatment reduces the internal stress of manganese-zinc ferrite, improves resistance, and significantly reduces the power loss of the material under high-frequency conditions. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 It is a typical curve diagram of the power loss variation with temperature at 1000kHz and 50mT of Example 1 of the present invention and Comparative Examples 1 and 2.

[0029] Figure 2 Typical curves of power loss versus temperature at 3000kHz and 30mT for Example 1 of the present invention and Comparative Examples 1 and 2. DETAILED DESCRIPTION

[0030] The present invention is further described below with reference to examples.

[0031] Example 1

[0032] A manganese-zinc ferrite material, comprising a main component and an auxiliary component, wherein the main component is composed of Fe2O3: 55.88mol%, ZnO: 0.31mol%, Co3O4: 0.33mol%, and the remainder is MnO;

[0033] The auxiliary components, calculated on the basis of the weight of the main components, include CaCO3: 1600ppm, SiO2: 80ppm, and Ta2O5: 1200ppm;

[0034] A method for preparing manganese-zinc ferrite comprises the following steps:

[0035] 1) Batching and mixing: According to the formula, the main ingredients were mixed with deionized water and wet ball milled. The ball milling time was 18 hours. The mass ratio of deionized water to powder was 2:1. In this case, the amount of powder was 200g, so the volume of deionized water was 400mL.

[0036] 2) Pre-calcination: The obtained slurry is dried and then pre-calcined in a muffle furnace at a pre-calcination temperature of 850° C. for 3 h.

[0037] 3) Secondary ball milling: According to the formula, the auxiliary ingredients, pre-burned powder and deionized water are wet-milled. The ball milling time is 18 hours. The mass ratio of deionized water to powder is 2:1. In this example, the amount of powder is 200g, so the volume of deionized water is 400mL.

[0038] 4) Granulation: Add a polyvinyl alcohol aqueous solution with a mass concentration of 10 wt % to the powder obtained by ball milling and drying, mix and granulate evenly to obtain granules; the weight ratio of the polyvinyl alcohol aqueous solution to the powder after ball milling is 10:1.

[0039] 5) Molding: Press the granulated granules into magnetic ring green bodies.

[0040] 6) Sintering: The green body is placed in a tubular furnace for sintering at a temperature of 1170°C, kept at that temperature for 6 hours, and cooled naturally. A balanced oxygen partial pressure is used throughout the cooling process.

[0041] 7) Heat aging treatment: Place the manganese-zinc ferrite magnetic ring in a tubular furnace with a heating rate of 2°C / min. Keep it at 200°C for 200 hours and then cool it to room temperature and take it out.

[0042] Example 2

[0043] A manganese-zinc ferrite material, comprising a main component and an auxiliary component, wherein the main component is composed of Fe2O3: 55.45mol%, ZnO: 0.29mol%, Co3O4: 0.37mol%, and the remainder is MnO;

[0044] The auxiliary components, calculated on the basis of the weight of the main components, include CaCO3: 1600ppm, SiO2: 80ppm, and Ta2O5: 1200ppm;

[0045] A method for preparing manganese-zinc ferrite comprises the following steps:

[0046] 1) Batching and mixing: according to the formula, the main ingredients were mixed with deionized water and wet ball milled. The ball milling time was 18 h. The mass ratio of deionized water to powder was 1.8:1. In this example, the amount of powder was 200 g, so the volume of deionized water was 360 mL.

[0047] 2) Pre-calcination: The obtained slurry is dried and then pre-calcined in a muffle furnace at a temperature of 850° C. for 3 h.

[0048] 3) Secondary ball milling: According to the formula, the auxiliary ingredients, pre-burned powder and deionized water are wet-milled. The ball milling time is 18 hours. The mass ratio of deionized water to powder is 2:1. In this example, the amount of powder is 200g, so the volume of deionized water is 400mL.

[0049] 4) Granulation: Add a polyvinyl alcohol aqueous solution with a mass concentration of 10 wt % to the powder obtained by ball milling and drying, mix and granulate evenly to obtain granules; the weight ratio of the polyvinyl alcohol aqueous solution to the powder after ball milling is 10:1.

[0050] 5) Molding: Press the granulated granules into magnetic ring green bodies.

[0051] 6) Sintering: The green body is placed in a tubular furnace and sintered at 1170°C, kept at the sintering temperature for 6 hours, and cooled naturally, with balanced oxygen partial pressure throughout the process.

[0052] 7) Thermal aging treatment: The manganese-zinc ferrite magnetic ring is placed in a tubular furnace for thermal aging at a heating rate of 2°C / min. After heat treatment at 200°C for 200 hours, the ring is cooled to room temperature and taken out.

[0053] Example 3

[0054] A manganese-zinc ferrite material, comprising a main component and an auxiliary component, wherein the main component is composed of Fe2O3: 56.35mol%, ZnO: 0.31mol%, Co3O4: 0.38mol%, and the remainder is MnO;

[0055] The auxiliary components, calculated on the basis of the weight of the main components, include CaCO3: 1600ppm, SiO2: 80ppm, and Ta2O5: 1200ppm;

[0056] A method for preparing manganese-zinc ferrite comprises the following steps:

[0057] 1) Batching and mixing: according to the formula, the main ingredients were mixed with deionized water and wet ball milled. The ball milling time was 18 h. The mass ratio of deionized water to powder was 2:1. In this example, the amount of powder was 200 g, so the volume of deionized water was 400 mL.

[0058] 2) Pre-calcination: The obtained slurry is dried and then pre-calcined in a muffle furnace at a temperature of 850° C. for 3 h.

[0059] 3) Secondary ball milling: According to the formula, the auxiliary ingredients, pre-burned powder and deionized water are wet-milled. The ball milling time is 18 hours. The mass ratio of deionized water to powder is 2:1. In this example, the amount of powder is 200g, so the volume of deionized water is 400mL.

[0060] 4) Granulation: Add a polyvinyl alcohol aqueous solution with a mass concentration of 10 wt % to the powder obtained by ball milling and drying, mix and granulate evenly to obtain granules; the weight ratio of the polyvinyl alcohol aqueous solution to the powder after ball milling is 10:1.

[0061] 5) Molding: Press the granulated granules into magnetic ring green bodies.

[0062] 6) Sintering: The green body is placed in a tubular furnace for sintering at a temperature of 1170°C, kept at that temperature for 6 hours, and cooled naturally. A balanced oxygen partial pressure is used throughout the cooling process.

[0063] 7) Heat aging treatment: Place the manganese-zinc ferrite magnetic ring in a tubular furnace with a heating rate of 2°C / min. Keep it at 190°C for 230 hours and then cool it to room temperature and take it out.

[0064] Example 4

[0065] A manganese-zinc ferrite material, comprising a main component and an auxiliary component, wherein the main component is composed of Fe2O3: 56.89mol%, ZnO: 0.29mol%, Co3O4: 0.34mol%, and the remainder is MnO;

[0066] The auxiliary components, calculated on the basis of the weight of the main components, include CaCO3: 1600ppm, SiO2: 80ppm, and Ta2O5: 1200ppm;

[0067] A method for preparing manganese-zinc ferrite comprises the following steps:

[0068] 1) Batching and mixing: according to the formula, the main ingredients were mixed with deionized water and wet ball milled. The ball milling time was 18 h. The mass ratio of deionized water to powder was 2:1. In this example, the amount of powder was 200 g, so the volume of deionized water was 400 mL.

[0069] 2) Pre-calcination: The obtained slurry is dried and then pre-calcined in a muffle furnace at a temperature of 850° C. for 3 h.

[0070] 3) Secondary ball milling: According to the formula, the auxiliary ingredients, pre-burned powder and deionized water are wet-milled. The ball milling time is 18 hours. The mass ratio of deionized water to powder is 2:1. In this example, the amount of powder is 200g, so the volume of deionized water is 400mL.

[0071] 4) Granulation: Add a polyvinyl alcohol aqueous solution with a mass concentration of 10 wt % to the powder obtained by ball milling and drying, mix and granulate evenly to obtain granules; the weight ratio of the polyvinyl alcohol aqueous solution to the powder after ball milling is 10:1.

[0072] 5) Molding: Press the granulated granules into magnetic ring green bodies.

[0073] 6) Sintering: The green body is placed in a tubular furnace for sintering at a temperature of 1170°C, kept at that temperature for 6 hours, and cooled naturally. A balanced oxygen partial pressure is used throughout the cooling process.

[0074] 7) Heat aging treatment: Place the manganese-zinc ferrite magnetic ring in a tubular furnace with a heating rate of 2°C / min. Keep it at 210°C for 180 hours and then cool it to room temperature and take it out.

[0075] Example 5

[0076] A manganese-zinc ferrite material, comprising a main component and an auxiliary component, wherein the main component is composed of Fe2O3: 54.75mol%, ZnO: 0.26mol%, Co3O4: 0.4mol%, and the remainder is MnO;

[0077] The auxiliary components, based on the weight of the main components, include CaCO3: 1400ppm, SiO2: 100ppm, Ta2O5: 1100ppm;

[0078] A method for preparing manganese-zinc ferrite comprises the following steps:

[0079] 1) Batching and mixing: according to the formula, the main ingredients were mixed with deionized water and wet ball milled. The ball milling time was 16 h. The mass ratio of deionized water to powder was 2.5:1. In this example, the amount of powder was 200 g, so the volume of deionized water was 500 mL.

[0080] 2) Pre-firing: The obtained slurry is dried and then pre-firing is carried out in a muffle furnace at a temperature of 900° C. for 3 h.

[0081] 3) Secondary ball milling: According to the formula, the auxiliary components, pre-burned powder and deionized water are wet-milled. The ball milling time is 16 hours. The mass ratio of deionized water to powder is 1.5:1. In this example, the amount of powder is 200g, so the volume of deionized water is 300mL.

[0082] 4) Granulation: Add a polyvinyl alcohol aqueous solution with a mass concentration of 12 wt% to the powder obtained after ball milling and drying, mix and granulate evenly to obtain granules; the weight ratio of the polyvinyl alcohol aqueous solution to the powder after ball milling is 8:1.

[0083] 5) Molding: Press the granulated granules into magnetic ring green bodies.

[0084] 6) Sintering: The green body is placed in a tubular furnace for sintering at a sintering temperature of 1160°C for 8 hours and then cooled naturally. A balanced oxygen partial pressure is used throughout the cooling process.

[0085] 7) Heat aging treatment: Place the manganese-zinc ferrite magnetic ring in a tubular furnace with a heating rate of 2°C / min. Keep it at 220°C for 190h and then cool it to room temperature and take it out.

[0086] Example 6

[0087] A manganese-zinc ferrite material, comprising a main component and an auxiliary component, wherein the main component is composed of Fe2O3: 56.95mol%, ZnO: 0.32mol%, Co3O4: 0.3mol%, and the remainder is MnO;

[0088] The auxiliary components, measured by weight of the main components, include CaCO3: 1800ppm, SiO2: 90ppm, and Ta2O5: 1000ppm;

[0089] A method for preparing manganese-zinc ferrite comprises the following steps:

[0090] 1) Batching and mixing: according to the formula, the main ingredients were mixed with deionized water and wet ball milled. The ball milling time was 24 h. The mass ratio of deionized water to powder was 2.25:1. In this example, the amount of powder was 200 g, so the volume of deionized water was 450 mL.

[0091] 2) Pre-calcination: The obtained slurry is dried and then pre-calcined in a muffle furnace at a temperature of 800° C. for 3 h.

[0092] 3) Secondary ball milling: According to the formula, the auxiliary components, pre-burned powder and deionized water are wet-milled. The ball milling time is 24 hours. The mass ratio of deionized water to powder is 2.25:1. In this example, the amount of powder is 200g, so the volume of deionized water is 450mL.

[0093] 4) Granulation: Add a polyvinyl alcohol aqueous solution with a mass concentration of 6 wt % to the powder obtained by ball milling and drying, mix evenly and granulate to obtain granules; the weight ratio of the polyvinyl alcohol aqueous solution to the powder after ball milling is 15:1.

[0094] 5) Molding: Press the granulated granules into magnetic ring green bodies.

[0095] 6) Sintering: The green body is placed in a tubular furnace for sintering at a temperature of 1180°C for 3 hours and then cooled naturally. A balanced oxygen partial pressure is used throughout the cooling process.

[0096] 7) Heat aging treatment: Place the manganese-zinc ferrite magnetic ring in a tubular furnace with a heating rate of 2°C / min. Keep it at 180°C for 250 hours and then cool it to room temperature and take it out.

[0097] Example 7

[0098] A manganese-zinc ferrite material, comprising a main component and an auxiliary component, wherein the main component is composed of Fe2O3: 56.95mol%, ZnO: 0.32mol%, Co3O4: 0.4mol%, and the remainder is MnO;

[0099] The auxiliary components, calculated on the basis of the weight of the main components, include CaCO3: 1500ppm, SiO2: 50ppm, and Ta2O5: 1400ppm;

[0100] A method for preparing manganese-zinc ferrite comprises the following steps:

[0101] 1) Batching and mixing: the main ingredients were mixed with deionized water according to the formula and wet ball milled. The ball milling time was 17 h. The mass ratio of deionized water to powder was 2.1:1. In this example, the amount of powder was 200 g, so the volume of deionized water was 420 mL.

[0102] 2) Pre-calcination: The obtained slurry is dried and then pre-calcined in a muffle furnace at a temperature of 820° C. for 3 h.

[0103] 3) Secondary ball milling: wet-mill the auxiliary ingredients, pre-burned powder and deionized water according to the formula. The ball milling time is 18 hours. The mass ratio of deionized water to powder is 1.9:1. In this example, the amount of powder is 200g, so the volume of deionized water is 380mL.

[0104] 4) Granulation: Add a polyvinyl alcohol aqueous solution with a mass concentration of 8 wt % to the powder obtained by ball milling and drying, mix and granulate evenly to obtain a granular material; the weight ratio of the polyvinyl alcohol aqueous solution to the powder after ball milling is 9:1.

[0105] 5) Molding: Press the granulated granules into magnetic ring green bodies.

[0106] 6) Sintering: The green body is placed in a tubular furnace for sintering at a temperature of 1165°C for 5 hours and then cooled naturally. A balanced oxygen partial pressure is used throughout the cooling process.

[0107] 7) Heat aging treatment: Place the manganese-zinc ferrite magnetic ring in a tubular furnace with a heating rate of 2°C / min. Keep it at 215°C for 195h and then cool it to room temperature and take it out.

[0108] Example 8

[0109] A manganese-zinc ferrite material, comprising a main component and an auxiliary component, wherein the main component is composed of Fe2O3: 54.75mol%, ZnO: 0.26mol%, Co3O4: 0.3mol%, and the remainder is MnO;

[0110] The auxiliary components, calculated on the basis of the weight of the main components, include CaCO3: 1700ppm, SiO2: 90ppm, and Ta2O5: 1300ppm;

[0111] A method for preparing manganese-zinc ferrite comprises the following steps:

[0112] 1) Batching and mixing: according to the formula, the main ingredients were mixed with deionized water and wet ball milled. The ball milling time was 22 h. The mass ratio of deionized water to powder was 1.9:1. In this example, the amount of powder was 200 g, so the volume of deionized water was 380 mL.

[0113] 2) Pre-calcination: The obtained slurry is dried and then pre-calcined in a muffle furnace at a temperature of 860° C. for 3 h.

[0114] 3) Secondary ball milling: According to the formula, the auxiliary components, pre-burned powder and deionized water are wet-milled. The ball milling time is 19 hours. The mass ratio of deionized water to powder is 1.6:1. In this example, the amount of powder is 200g, so the volume of deionized water is 320mL.

[0115] 4) Granulation: Add a polyvinyl alcohol aqueous solution with a mass concentration of 12 wt % to the powder obtained by ball milling and drying, mix and granulate evenly to obtain granules; the weight ratio of the polyvinyl alcohol aqueous solution to the powder after ball milling is 12:1.

[0116] 5) Molding: Press the granulated granules into magnetic ring green bodies.

[0117] 6) Sintering: The green body is placed in a tubular furnace for sintering at a temperature of 1175°C for 6.5 hours and then cooled naturally. A balanced oxygen partial pressure is used throughout the cooling process.

[0118] 7) Heat aging treatment: Place the manganese-zinc ferrite magnetic ring in a tubular furnace with a heating rate of 2°C / min. Keep it at 215°C for 240 hours and then cool it to room temperature and take it out.

[0119] Comparative Example 1

[0120] The preparation process of the comparative example is the same as that of the embodiment, and the main components are Fe2O3: 53.86mol%, ZnO: 0.39mol%, Co3O4: 0.53mol%, and the balance is MnO;

[0121] The auxiliary components of the comparative example are calculated by weight of the main components, including CaCO3: 1600ppm, SiO2: 80ppm, Ta2O5: 1200ppm;

[0122] The preparation method of the comparative example comprises the following steps:

[0123] 1) Batching and mixing: according to the formula, the main ingredients were mixed with deionized water and wet ball milled. The ball milling time was 18 h. The mass ratio of deionized water to powder was 2:1. In this example, the amount of powder was 200 g, so the volume of deionized water was 400 mL.

[0124] 2) Pre-calcination: The obtained slurry is dried and then pre-calcined in a muffle furnace at a temperature of 850° C. for 3 h.

[0125] 3) Secondary ball milling: According to the formula, the auxiliary ingredients, pre-burned powder and deionized water are wet-milled. The ball milling time is 18 hours. The mass ratio of deionized water to powder is 2:1. In this example, the amount of powder is 200g, so the volume of deionized water is 400mL.

[0126] 4) Granulation: Add a polyvinyl alcohol aqueous solution with a mass concentration of 10 wt % to the powder obtained by ball milling and drying, mix and granulate evenly to obtain granules; the weight ratio of the polyvinyl alcohol aqueous solution to the powder after ball milling is 10:1.

[0127] 5) Molding: Press the granulated granules into magnetic ring green bodies.

[0128] 6) Sintering: The green body is placed in a tubular furnace for sintering at a temperature of 1170°C, kept at that temperature for 6 hours, and cooled naturally. A balanced oxygen partial pressure is used throughout the cooling process.

[0129] 7) Heat aging treatment: Place the manganese-zinc ferrite magnetic ring in a tubular furnace with a heating rate of 2°C / min. Keep it at 200°C for 200 hours and then cool it to room temperature and take it out.

[0130] The difference between Comparative Example 1 and the embodiment is that the content of the components exceeds the range of the main component and the auxiliary component.

[0131] Comparative Example 2

[0132] The preparation process of the comparative example is the same as that of the embodiment, and the main components are Fe2O3: 55.78mol%, ZnO: 0.32mol%, Co3O4: 0.36mol%, and the balance is MnO;

[0133] The auxiliary components of the comparative example are calculated by weight of the main components, including CaCO3: 1600ppm, SiO2: 80ppm, Ta2O5: 1200ppm;

[0134] The preparation method of the comparative example comprises the following steps:

[0135] 1) Batching and mixing: according to the formula, the main ingredients were mixed with deionized water and wet ball milled. The ball milling time was 18 h. The mass ratio of deionized water to powder was 2:1. In this example, the amount of powder was 200 g, so the volume of deionized water was 400 mL.

[0136] 2) Pre-calcination: The obtained slurry is dried and then pre-calcined in a muffle furnace at a temperature of 850° C. for 3 h.

[0137] 3) Secondary ball milling: According to the formula, the auxiliary ingredients, pre-burned powder and deionized water are wet-milled. The ball milling time is 18 hours. The mass ratio of deionized water to powder is 2:1. In this example, the amount of powder is 200g, so the volume of deionized water is 400mL.

[0138] 4) Granulation: Add a polyvinyl alcohol aqueous solution with a mass concentration of 10 wt % to the powder obtained by ball milling and drying, mix and granulate evenly to obtain granules; the weight ratio of the polyvinyl alcohol aqueous solution to the powder after ball milling is 10:1.

[0139] 5) Molding: Press the granulated granules into magnetic ring green bodies.

[0140] 6) Sintering: The green body is placed in a tubular furnace for sintering at a temperature of 1170°C, kept at that temperature for 6 hours, and cooled naturally. A balanced oxygen partial pressure is used throughout the cooling process.

[0141] 7) Heat aging treatment: Comparative Example 2 was not subjected to heat aging treatment.

[0142] The difference between Comparative Example 2 and the embodiment is that the thermal aging process exceeds the implementation scope.

[0143] The P of the embodiments and comparative examples was measured using the BH detector SY-8218 produced by IWATSU Corporation of Japan. cv The main components and auxiliary components of the embodiments and comparative examples were calibrated using a Rigaku ZXS primus series X-ray fluorescence spectrometer; the test temperature was set using an ESPEC SU-641 oven, and the error was controlled within ±0.1° C. The results of embodiments 1-4 and comparative examples 1-2 are shown in Table 1.

[0144] Table 1

[0145]

[0146] From the data in Table 1, it can be seen that the main components and thermal aging processes of Examples 1 to 4 are within the specified range of the present invention. Examples 1 and 2 are within the specified range, and the main components are different. The main components of Examples 1, 3, and 4 are within the specified range, and the temperature and time of the thermal aging process are different. The embodiments all ensure that the power consumption at 25°C is not higher than 40kW·m under the conditions of 1000kHz and 50mT. -3 , the power consumption at 100℃ is not higher than 50kW·m -3 ; Under the conditions of 3000kHz, 30mT, the power consumption at 25℃ is not higher than 270kW·m -3 , the power consumption at 100℃ is not higher than 340kW·m -3. It meets the low power consumption characteristics of the material at high frequencies.

[0147] From the data in Table 1, it can be seen that the main components of Comparative Example 1, Fe2O3 and ZnO, significantly exceed the scope of the invention. Although the heat aging treatment within the limited range was adopted, the loss of this comparative example at 1000kHz, 50mT was significantly increased compared with the embodiment. The main components of Comparative Example 2 are within the scope of the invention, but the heat aging process is not adopted. Its power loss at 1000kHz, 50mT and 3000kHz, 30mT is significantly increased.

[0148] After testing, the manganese-zinc ferrites prepared in Examples 5-8 are guaranteed to have a power consumption of no more than 40kW·m at 25°C under the conditions of 1000kHz and 50mT. -3 , the power consumption at 100℃ is not higher than 50kW·m -3 ; Under the conditions of 3000kHz, 30mT, the power consumption at 25℃ is not higher than 270kW·m -3 , the power consumption at 100℃ is not higher than 340kW·m -3 , which can meet the low power consumption characteristics of the material at high frequencies.

[0149] The above implementation modes are not limitations of the present invention, and the present invention is not limited to the above examples. Changes, modifications, additions or substitutions made by technicians in this technical field within the scope of the technical solution of the present invention also belong to the protection scope of the present invention.

Claims

1. A method for preparing a high-frequency low-loss manganese-zinc ferrite material, characterized in that: The following steps are included: 1) accurately weighing the main components according to the proportion and mixing them with deionized water, and wet-milling to obtain a uniformly distributed slurry; drying the slurry to obtain a powder with uniform particle distribution; wherein the main components, in terms of molar percentage, include Fe2O3: 54.75-56.95mol%, ZnO: 0.26-0.32mol%, Co3O4: 0.30-0.40mol%, and the remainder is MnO; 2) placing the powder obtained in step 1) in a muffle furnace for pre-sintering; 3) accurately weighing the auxiliary components according to the proportion, mixing with the pre-sintered powder obtained in step 2) and deionized water, and wet-milling to obtain a uniformly distributed slurry; drying the slurry to obtain a powder with uniform particle distribution; wherein the auxiliary components, in terms of mass percentage of the main components, include CaCO3: 1400ppm-1800ppm, SiO2: 50ppm-100ppm, and Ta2O5: 1000ppm-1400ppm; 4) granulating and molding the powder obtained in step 3) and then sintering it at high temperature in a tube furnace; 5) placing the high-temperature sintered material obtained in step 4) in a tubular furnace for long-term heat preservation and thermal aging treatment.

2. The method for preparing the high-frequency low-loss manganese-zinc ferrite material according to claim 1, characterized in that: The deionized water used in step 1) is in a mass ratio of 1.5:1 to 2.5:1 to the powder mass, and the ball milling time is 16h-24h.

3. The method for preparing the high-frequency low-loss manganese-zinc ferrite material according to claim 1, characterized in that: In step 2), the pre-sintering temperature is 800° C. to 900° C., the heating rate is 2° C. / min, the holding time is 3 hours, and the pre-sintering material is obtained by naturally cooling after pre-sintering.

4. The method for preparing the high-frequency low-loss manganese-zinc ferrite material according to claim 1, characterized in that: The deionized water used in step 3) is in a mass ratio of 1.5:1 to 2.5:1 to the mass of the powder, and the ball milling time is 16h-24h.

5. The method for preparing high-frequency low-loss manganese-zinc ferrite according to claim 1, characterized in that: Granulation in step 4) is specifically as follows: Add polyvinyl alcohol aqueous solution to the powder obtained in step 3), mix well and granulate to obtain granular material; The mass concentration of the polyvinyl alcohol aqueous solution used is 6%wt-12wt%; the mass ratio of the polyvinyl alcohol aqueous solution to the powder is 8:1-15:

1.

6. The method for preparing the high-frequency low-loss manganese-zinc ferrite material according to claim 1, characterized in that: In step 4), the green density of the ferrite magnetic ring obtained after molding is 5.0±0.1g·cm -3 .

7. The method for preparing the high-frequency low-loss manganese-zinc ferrite material according to claim 1, characterized in that: Step 4) sintering temperature is 1160° C.-1180° C., holding time is 3 h to 8 h, natural cooling is performed, and balanced oxygen partial pressure is used in the cooling process to obtain manganese-zinc ferrite material.

8. The method for preparing the high-frequency low-loss manganese-zinc ferrite material according to claim 1, characterized in that: Step 5) The heat aging temperature is 180°C-220°C, the heating rate is 2°C / min, and the heat aging time is 180h-250h.

9. The method for preparing the high-frequency low-loss manganese-zinc ferrite material according to claim 1, characterized in that: The main components, in terms of molar percentage, include Fe2O3: 55.88 mol%, ZnO: 0.31 mol%, Co3O4: 0.33 mol%, and the remainder is MnO; The auxiliary components, calculated in terms of mass percentage of the main components, include CaCO3: 1600ppm, SiO2: 80ppm, and Ta2O5: 1200ppm.

10. A high-frequency, low-loss manganese-zinc ferrite material prepared by the method for preparing the high-frequency, low-loss manganese-zinc ferrite material according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Low-temperature sintered high-frequency low-loss MnZn power ferrite and preparation method thereof

    CN118184328A

  • High-Bs low-loss megahertz manganese zinc power ferrite and preparation method thereof

    CN118184329A

  • Manganese zinc ferrite material and preparation method thereof

    CN107021746A

  • Mn-Zn SYSTEM FERRITE MAGNETIC CORE AND PREPARATION METHOD THEREOF

    CN108885938A

  • High-permeability low-loss iron-based soft magnetic composite material and preparation method thereof

    CN110136910A

Cited By

  • Low dielectric constant and high thermal conductivity LTCC material and preparation method thereof

    CN121342500A

  • A low dielectric constant and high thermal conductivity LTCC material and its preparation method

    CN121342500B

  • High-temperature high-frequency large-magnetic-field low-loss soft magnetic ferrite material as well as preparation method and application thereof

    CN122212707A